Unfit for Democracy : The Roberts Court and the Breakdown of American Politics - Gottlieb, Stephen E. (Book collections on Project MUSE., 2016)
Asked if the country was governed by a republic or a monarchy, Benjamin Franklin replied, 'A republic, if you can keep it.' Since its founding, Americans have worked hard to nurture and protect their hard-won democracy. And yet few consider the role of constitutional law in America's survival. Stephen Gottlieb argues that constitutional law without a focus on the future of democratic government is incoherent, illogical and contradictory.